Mapping Trends of Literature in Energy Policy in Indonesia: A Bibliometric Analysis - Sajida Sajida (Indonesian Association for Public Administration, 2022)
Energy policy recently became an issue that has been highlighted by various parties, including academics in Indonesia. This coincides with the signs of the climate crisis, and the environmental damage that is affected by energy management. Although, there have been many studies discussing it, so far, there has been no research showing the direction of energy policy in Indonesia. Thus, this paper aims to map the trends in the literature. Bibliometric analysis is used to map topics raised from various research article by looking at the most common keywords, and identifying the most cited and productive sources. Per the results, the discussion of renewable energy and related topics became the dominant issue in the mapping of this main topic from 2003 to 2021. Then Energy Policy Journal the most cited reference, and the Iop Conference Series: Earth and Environmental Science became the most productive source. The results of this study indicate indirectly, how far Indonesia's energy policy has developed periodically. Including how Indonesia amid various countries has been campaigning for renewable energy that pays attention to the environment. Besides, this research also provides future research agendas for others to examine energy policy in Indonesia from various perspectives that have not been studied previously.